The Effects Of International Trade On Macroeconomic Stability In African Countries - Okah-Efogo, FranÃ§oise (Mediterranean Journal of Social Sciences, 2012)
Trying to explain the recent financial and global crisis effects in Africa, different authors demonstrate that international trade has played a key role as a driving channel. The aim of our work is, subsequently, to assess the effects of international trade indicators on African macroeconomic stability. This study is justified by the dependence of these countries to the fluctuations of international business flows. The baseline assumption of the paper is that international trade may induce high volatility in African countries unduly the type of exchange rate arrangement. The set of international trade indicators include indicators of commercial flows (exportations, importations, and openness) and other indicators (terms of trade, exchange rate). Growth volatility is measured by the conditional variance of per capita GDP growth rate. The conditional variance is extracted using a SAARCH model for each country. Then international trade indicators are included in the growth volatility model with a set of control variables. The results show that between 1980 and 2010, international trade is an important determinant of growth instability in African countries whatever the exchange rate regime.